Electoral Credit Supply Cycles Among German Savings Banks - Reint E. Gropp; Vahid Saadi (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
In this note we document political lending cycles for German savings banks. We find that savings banks on average increase supply of commercial loans by exteuro7.6 million in the year of a local election in their respective county or municipality (Kommunalwahl). For all savings banks combined this amounts to exteuro3.4 billion (0.4% of total credit supply in Germany in a complete electoral cycle) more credit in election years. Credit growth at savings banks increases by 0.7 percentage points, which corresponds to a 40% increase relative to non-election years. Consistent with this result, we also find that the performance of the savings banks follows the same electoral cycle. The loans that the savings banks generate during election years perform worse in the first three years of maturity and loan losses tend to be realized in the middle of the election cycle.
urn:nbn:de:gbv:3:2-51115
Keywords: 330; German savings banks; municipality